Editorial (diségno, 2024)
The topic of this issue 15 focuses on the theme of landscape representation and is located in an area common to various disciplines in the relationship between nature and culture; it is a complex area, rich in articulations and implications, but structurally permanent,  even if historically variable. [read more]